Стимуляторы речевой активности - Каленова, И.С.; Пазылова, А.А.; Байбол, Р. (My University, 2016)
The article deals with the study of Russian as a foreign language. The article discusses the implementation triyazychiya because today it is an important aspect of the language policy of the Republic of Kazakhstan and is considered a fundamental principle of the educational process. This process determines the development of functional literacy, communication skills and ability to think critically. Objective historical regularity now is to increase the requirements for the education of the person.
Keywords: trilingualism; communication; outlook; speech activity